Histories of life: the biographical narrative between self-knowledge and accounting for social life (Praxis Educativa, 2014)
This paper sets in context the biographical-narrative research and life stories/histories as forms of subjectivity, of making visible the voice of the ordinary people and highlighting the situated and complex nature of social problem. From here, the two dominant traditions in this kind of research are discussed. One of French influence, in which the development of the (auto) biographical stories occurs in the professional development process and as a way to narrate oneself and make explicit the components of the subjectivity constitution. And another, more rooted in English-speaking countries, where life stories play an important role in the Social Sciences as a way to explain and understand the subjective dimensions of social phenomena. The paper concludes by exploring how we approach (auto) biographical narratives and life histories in the quality research group ESBRINA and the possibilities offered to generate forms of knowledge based on the personal accounts of the participants in our research projects and ourselves as researchers.
Keywords: narrative research; biographical research; teacher professional development; narrativity